The Influence of Market Orientation, Product Innovation and Business Creativity on Marketing Performance in MSMEs (Study on MSMEs Manding District) - Dewi, Ratna; Kustiningsih, Nanik (International Journal of Science, Engineering, and Information Technology, 2023)
This research aims to examine the influence of market orientation, product innovation and business actor creativity on marketing performance in MSMEs. The variables used in this research are market orientation, product innovation, and business actor creativity as independent variables, and marketing performance as the dependent variable. This research is quantitative research. The data source in this research is primary data where the data collection method uses a questionnaire method which is distributed to all MSMEs in Manding District which operate in the culinary sector (cassava chips). The number of samples used was 130 respondents. By processing primary data using the Statistical Package For Social Science (SPSS) version 22 analysis technique. The results of this research show that market orientation has a positive and significant effect on marketing performance. Product innovation has a positive and significant effect on marketing performance. The creativity of business actors has a positive and significant effect on marketing performance. Market orientation, product innovation and business actor creativity influence marketing performance simultaneously.